Evaluation of Antimicrobial Activity of Newly Prepared Calcium Oxide Based Nanosealer Using Agar Diffusion Test (Mustansiria Dental Journal, 2022)
Aim of the study: The antimicrobial activity of a root canal sealer can increase the success rate of endodontic treatments. The key of antimicrobial properties of calcium based sealers laid in their composition and alkalinity. The invention and applications of newer materials are quintessential in every field especially in endodontics. This reality has led to growing interest in the use of biomaterials products that comprised of both mineral and organic components as those in the teeth. This study was performed to assess the antibacterial activity of newly prepared calcium oxide based nanosealer and compare the result with BioRoot sealerMaterials and methods: The CaO nanopowder was firstly prepared from calcinated cowrie seashell using ball milling and ultrasonic irradiation methods, and then the CaO nanopowder was used as the main component in the preparation of an experimental nanosealer powder part. After several pilot studies, the final formula for the prepared sealer that gave the best clinical sealer consistency and properties within the limits of ANSI/ADA Specification No.57/2012 was as the following. The powder part consists mainly of nano CaO (44%) in addition to glutamic amino acid, zirconium oxide (20nm), and silica oxide (15-20) nm, while the liquid part consists mainly from distilled water in addition to propylene glycol. The Antimicrobial activity of the prepared sealer was evaluated by agar diffusion test against E.faecalis and E.faecium, after 1, 2, 3, and 7 days of incubation at 37˚C. Zone of bacterial inhibition was measured and analyzed statistically using Independent sample t – test at (p=0.05) levels.